Mechanisms for the Development of Heart Failure and Improvement of Cardiac Function by Angiotensin-Converting Enzyme Inhibitors : N/A - Bhullar, Sukhwinder K; Shah, Anureet K; Dhalla, Naranjan S (Scripta Medica, 2022)
Angiotensin-converting enzyme (ACE) inhibitors, which prevent the conversion of angiotensin I to angiotensin II, are well-known for the treatments of cardiovascular diseases, such as heart failure, hypertension and acute coronary syndrome. Several of these inhibitors including captopril, enalapril, ramipril, zofenopril and imidapril attenuate vasoconstriction, cardiac hypertrophy and adverse cardiac remodeling, improve clinical outcomes in patients with cardiac dysfunction and decrease mortality. Extensive experimental and clinical research over the past 35 years has revealed that the beneficial effects of ACE inhibitors in heart failure are associated with full or partial prevention of adverse cardiac remodeling. Since cardiac function is mainly determined by coordinated activities of different subcellular organelles, including sarcolemma, sarcoplasmic reticulum, mitochondria and myofibrils, for regulating the intracellular concentration of Ca2+ and myocardial metabolism, there is ample evidence to suggest that adverse cardiac remodelling and cardiac dysfunction in the failing heart are the consequence of subcellular defects. In fact, the improvement of cardiac function by different ACE inhibitors has been demonstrated to be related to the attenuation of abnormalities in subcellular organelles for Ca2+-handling, metabolic alterations, signal transduction defects and gene expression changes in failing cardiomyocytes. Various ACE inhibitors have also been shown to delay the progression of heart failure by reducing the formation of angiotensin II, the development of oxidative stress, the level of inflammatory cytokines and the occurrence of subcellular defects. These observations support the view that ACE inhibitors improve cardiac function in the failing heart by multiple mechanisms including the reduction of oxidative stress, myocardial inflammation and Ca2+-handling abnormalities in cardiomyocytes.
Keywords: ACE inhibitors; Adverse cardiac remodelling; Subcellular defects in myocardium; Cardiac dysfunction in failing heart; Ca2 -handling abnormalities; Oxidative stress and inflammation